Investigation of the experience of foodborne illness and estimation of the incidence of foodborne disease in South Korea. (January 2015) - Kim, Yong Soo; Lee, Soon Ho; Kim, Soon Han; Joo, Yongsung; Bahk, Gyung Jin
Abstract: The national incidence of foodborne illness reported by public health surveillance systems is lower than the actual incidence due to underdiagnosis and underreporting. Therefore, it is necessary to estimate the actual cases of foodborne illness at a national level. This study used a simple method of polling and estimation that overcomes the problem of lack of data. A national survey of the experience, diagnosis with and/or treatment for, and/or hospitalization for foodborne illness among a representative sample in South Korea was conducted. The survey results were then used to estimate the actual incidence of foodborne disease using a simulation method that expressed the estimated values as 95% confidence intervals (CI) to address uncertainty. Among the 1439 respondents for whom valid data were collected, 19.18% had experienced, 3.13% had been diagnosed with and/or treated for, and 0.28% had been hospitalized for foodborne disease. Using these results, it was estimated that 9.59 (95% CI: 8.57–10.61) million individuals experience, 1.56 (95% CI: 1.11–2.01) million are diagnosed with and/or treated for, and 140, 000 (95% CI: 30, 000–280, 000) are hospitalized for foodborne diseases annually in South Korea. The estimated number of patients hospitalized for foodborne disease is approximately 20 times higher than that of the number of reported cases in Ministry of Korean Food and Drug Safety, indicating that a large number of cases are unreported. Consideration of these results will be useful for the prevention and control of foodborne disease in South Korea and allow for international comparison of the incidence of foodborne illness. Highlights: A telephone survey of foodborne illness experience was conducted. Of the respondents, 19.2%, 3.1%, and 0.3% were experienced, diagnosed and hospitalized. An estimated 140, 000 are hospitalized, and is 20 times higher than reported. These results will be useful for the control of foodborne disease.